Phase I study of ABBV-428, a mesothelin-CD40 bispecific, in patients with advanced solid tumors. Issue 2 (19th February 2021) - Luke, Jason J; Barlesi, Fabrice; Chung, Ki; Tolcher, Anthony W; Kelly, Karen; Hollebecque, Antoine; Le Tourneau, Christophe; Subbiah, Vivek; Tsai, Frank; Kao, Steven; Cassier, Philippe A; Khasraw, Mustafa; et al.
Abstract : Background: CD40 agonist immunotherapy can potentially license antigen-presenting cells to promote antitumor T-cell activation and re-educate macrophages to destroy tumor stroma. Systemic administration of CD40 agonists has historically been associated with considerable toxicity, providing the rationale for development of tumor-targeted immunomodulators to improve clinical safety and efficacy. This phase I study assessed the safety, tolerability, preliminary antitumor activity, and preliminary biomarkers of ABBV-428, a first-in-class, mesothelin-targeted, bispecific antibody designed for tumor microenvironment-dependent CD40 activation with limited systemic toxicity. Methods: ABBV-428 was administered intravenously every 2 weeks to patients with advanced solid tumors. An accelerated titration (starting at a 0.01 mg/kg dose) and a 3+3 dose escalation scheme were used, followed by recommended phase II dose cohort expansions in ovarian cancer and mesothelioma, tumor types associated with high mesothelin expression. Results: Fifty-nine patients were treated at doses between 0.01 and 3.6 mg/kg. The maximum tolerated dose was not reached, and 3.6 mg/kg was selected as the recommended phase II dose. Seven patients (12%) reported infusion-related reactions. Treatment-related grade ≥3 treatment-emergent adverse events were pericardial effusion, colitis, infusion-related reaction, and pleural effusion (n=1 each, 2%), with no cytokine release syndrome reported. The pharmacokinetic profile demonstrated roughly dose-proportional increases in exposure from 0.4 to 3.6 mg/kg. Best response was stable disease in 9/25 patients (36%) treated at the recommended phase II dose. CD40 receptor occupancy >90% was observed on peripheral B-cells starting from 0.8 mg/kg; however, no consistent changes from baseline in intratumoral CD8+ T-cells, programmed death ligand-1 (PD-L1+) cells, or immune-related gene expression were detected post-ABBV-428 treatment (cycle 2, day 1). Mesothelin membrane staining showed greater correlation with progression-free survival in ovarian cancer and mesothelioma than in the broader dose escalation population. Conclusions: ABBV-428 monotherapy exhibited dose-proportional pharmacokinetics and an acceptable safety profile, particularly for toxicities characteristic of CD40 agonism, illustrating that utilization of a tumor-targeted, bispecific antibody can improve the safety of CD40 agonism as a therapeutic approach. ABBV-428 monotherapy had minimal clinical activity in dose escalation and in a small expansion cohort of patients with advanced mesothelioma or ovarian cancer. Trial registration number: NCT02955251 .